Business environment as a determining factor for foreign direct investment (Numerus academy review, 2026)
Foreign direct investment is receiving great attention in various countries, as it hasan impact on economic development, so that competition to attract foreign and domesticinvestments has become a prominent priority for economic policy makers in most countries of the world. Therefore, all countries have tended to improve theirattractiveness to foreign direct investment, including developing countries, especially Algeria, to speed up the modification and reform of the business environment, which is characterized by intense competition in attracting foreign direct investment flows and despite various adjustments and reforms. Algeria has not yet become an important magnetfor foreign direct investment compared to other developing countries, reflecting an environment of business that is not fit for activity.